Tachykinins, new players in the control of reproduction and food intake: A comparative review in mammals and teleosts - Campo, Aurora; Dufour, Sylvie; Rousseau, Karine (Frontiers in Endocrinology, 2022)
In vertebrates, the tachykinin system includes tachykinin genes, which encode one or two peptides each, and tachykinin receptors. The complexity of this system is reinforced by the massive conservation of gene duplicates after the whole genome duplication events that occurred in vertebrates and furthermore in teleosts. Added to this, the expression of the tachykinin system is more widespread than first thought, being found beyond brain and gut. The discovery of the co-expression of neurokinin B, encoded by tachykinin 3 gene, and kisspeptin/dynorphin in neurons involved in the generation of GnRH pulse in mammals, put a spotlight on the tachykinin system in vertebrate reproductive physiology. As food intake and reproduction are linked processes, and considering that hypothalamic hormones classically involved in the control of reproduction are reported to regulate also appetite and energy homeostasis, it is of interest to look at the potential involvement of tachykinins in these two major physiological functions. The purpose of this review is thus to provide first a general overview of the tachykinin system in mammals and teleosts, before giving a state-of-the-art on the different levels of action of tachykinins in the control of reproduction and food intake. This work has been conducted with a comparative point-of-view, highlighting the major similarities and differences of tachykinin systems and actions between mammals and teleosts.